A problemática da conceituação do Complexo Estilístico Serra Talhada da tradição nordeste de pinturas rupestres, no Parque Nacional Serra da Capivara-PI: um estudo de caso - Oliveira, Gabriel Frechiani de (2018)
The present work has the purpose of studying the similarities and differences of the Complexo Estilístico Serra Talhada, from the Nordeste tradition of rock paintings in the Park National Serra Capivara. O Park National Serra da Capivara is located in the Southeast region of Piauí, covering the municipalities of Coronel José Dias, Brejo do Piauí, São Raimundo Nonato and João Costa, thus comprising the area of approximately 130,000 hectares. O Parque Nacional Serra da Capivara is an integral conservation unit, protected by federal laws and possessing a great diversity of archaeological and palaeontological records in the place, including rock art,classified in three paintings traditions: Nordeste, Agreste and Geométrica. The general objective of this research is to show the similarities and differences in the Complexo EstilísticoSerra Talhada, belonging to the Nordeste tradition of paintings of the other styles (Serra daCapivara and Serra Branca) present in the place. The main justification for this research is to seek identification and differentiation of this style of the Nordeste tradition, considering its complexity and heterogeneity, which have been repetitive for decades without a study of the Serra da Capivara and Serra Branca style delimitation. The scientific methodology adopted is based on bibliographical and documentary research, associated to the field research in 51 archaeological sites of Park National Serra da Capivara, more specifically Serra da Capivara, Serra Talhada, Serra Branca, Veredão and Congo. At the end of the work, we hope to contribute to the development of archaeological research in the region, in particular, in order to elucidate the problem of similarities and differences in the Serra Talhada stylistic complex.